Volatility Spillovers between Oil Prices and Stock Returns in Developing Countries - Massadikov, Khairulla (International Journal of Energy Economics and Policy, 2021)
Risk and uncertainty have always been an important issue for investors, researchers and policymakers. Thus, the explanation of the mechanism of spreading volatility between different markets has been the focus of attention by researchers. Determining the return and volatility interaction between oil prices and stock markets will be useful not only for pricing and hedging financial assets, but also for detecting and interpreting the reflection of the problems arising in the oil industry on the country’s economies. In this study, the VAR-GARCH model introduced by Ling and McAleer (2003) was used to determine the interaction between oil prices and stock markets in terms of return and volatility for developing countries (BRICS-T). The reason for choosing this model is to reveal whether the shocks and volatility in these markets have a transitional effect. Keywords: oil price, stock return, volatility spillovers, VAR-GARCH model JEL Classifications: G11, G15, Q4 DOI: https://doi.org/10.32479/ijeep.11117